2015
DOI: 10.1016/j.jamda.2015.03.026
|View full text |Cite
|
Sign up to set email alerts
|

What Happens to Patients When They Fracture Their Hip During a Skilled Nursing Facility Stay?

Abstract: Objectives To characterize outcomes of patients experiencing a fall and subsequent hip fracture while in a nursing home (NH) receiving skilled nursing facility (SNF) services. Design Observational study. Participants Short-stay fee-for-service Medicare beneficiaries who experienced their first hip fracture during a SNF stay. Measurements Outcomes measured in the 90 days after the hip fracture hospitalization included community discharge (with a stay in the community < 30 days), successful community disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…This finding supports the conclusions of Duncan and Velozo 39 and Leland and colleagues. 40 Almost 10 years ago, Duncan and Velozo concluded that although validated outcome measures exist in the postacute rehabilitation period, there is a lack of quality indicators to actually assess the care delivered in the USA. 39 Similar conclusions were made more recently by Leland and colleagues, who stated that owing to the limited number of quality of care measures in the postacute period, stakeholders (ie, patients, families, payers and providers) are left without required information to make important decisions for hip fracture rehabilitation in the USA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports the conclusions of Duncan and Velozo 39 and Leland and colleagues. 40 Almost 10 years ago, Duncan and Velozo concluded that although validated outcome measures exist in the postacute rehabilitation period, there is a lack of quality indicators to actually assess the care delivered in the USA. 39 Similar conclusions were made more recently by Leland and colleagues, who stated that owing to the limited number of quality of care measures in the postacute period, stakeholders (ie, patients, families, payers and providers) are left without required information to make important decisions for hip fracture rehabilitation in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…39 Similar conclusions were made more recently by Leland and colleagues, who stated that owing to the limited number of quality of care measures in the postacute period, stakeholders (ie, patients, families, payers and providers) are left without required information to make important decisions for hip fracture rehabilitation in the USA. 106 Two important potential indictors for quality of rehabilitative care in the postacute period that were found in the literature were functional ability and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Among the eight reviewed articles, five were cross sectional studies (Lee, 2006; Leland et al 2015; Madigan et al, 2012; Scharpf & Madigan, 2010; Wysocki, Thomas & Mor, 2015), one quasi experimental study (Tinetti, Charpentier, Gottschalk & Baker., 2012), one prospective cohort study (Thygesen, Saevereid, Linstrom, Nygaard & Engedal, 2009) and one retrospective cohort study (Jung, Trivedi, Grabowski et al, 2016). Four of the studies were conducted in HHC settings (Thygesen et al, 2009; Scharpf et al, 2010; Madigan et al, 2012 & Tinetti et al, 2012) and four in SNF (Lee, 2006; Wysocki et al, 2015; Leland et al, 2015 & Jung et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Four of the studies were conducted in HHC settings (Thygesen et al, 2009; Scharpf et al, 2010; Madigan et al, 2012 & Tinetti et al, 2012) and four in SNF (Lee, 2006; Wysocki et al, 2015; Leland et al, 2015 & Jung et al, 2016). Of the 4 HHC studies, one was conducted in a single site (Tinetti et al 2012), one in a multi city HHC in Norway (Thygesen et al, 2009), and 2 used large representative samples from the United States (Madigan et al 2012; Scharpf, et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation